A Review on Fabrication Methods and Research Progress of Superhydrophobic Silicone Rubber Materials. Issue 1 (16th November 2020) - Wang, Guangfei; Li, Anling; Zhao, Wen; Xu, Zehua; Ma, Yongwei; Zhang, Fangyuan; Zhang, Yanbin; Zhou, Jin; He, Qiang
Abstract: Silicone rubber materials have excellent comprehensive properties and are widely used in outdoor insulation, aerospace, and other fields. Due to its low surface energy and the appearance of biomimetic superhydrophobic materials, silicone rubber has become one of the popular materials in the field of superhydrophobicity. Superhydrophobic silicone rubber materials play an irreplaceable role in a wide range of applications such as long‐distance high‐voltage power transmission and high‐speed rail transportation. In this paper, research on superhydrophobic materials, including typical fabrication methods, is summarized to provide an overview of the up‐to‐date research state and progress in detail. Abstract : Silicone rubber is widely used in the manufacture of superhydrophobic materials. In this paper, the preparation methods of superhydrophobic silicone rubber materials are introduced, including template method, spraying method, spin‐coating, dip‐coating and sieve‐deposition method, laser irradiation/etching, physical deposition method, particles filled method, etc. The application field, existing problems, and development prospect of superhydrophobic silicone rubber materials are described.